Transformasi Digital LPP TVRI dalam Meningkatkan Layanan Penyiaran Publik: Studi Kasus LPP TVRI Jambi - Wulandari, Rosa Jenita; Maulana, Rio Yusri; Lega, Michael (Kolaborasi : Jurnal Administrasi Publik, 2024)
In today’s digital era, television stations face competition not only from other traditional broadcasters but also from the growing presence of social media and digital platforms, which are increasingly favored by the public. Digital transformation has become essential for maintaining relevance in a highly competitive broadcasting landscape. This study explores how LPP TVRI Jambi’s digital transformation enhances public broadcasting services, examining both supportive and hindering factors in the process. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, and analyzed through the stages of Data Collection, Data Condensation, Data Display, and Conclusion Drawing/Verification. The findings indicate that LPP TVRI Jambi’s digital transformation, aligned with Mergel’s theory, encompasses motivations, objectives, processes, and outcomes. Key drivers include external factors such as government policies and increased competition, along with internal initiatives driven by team creativity. Transformation efforts focus on establishing new policies, procedures, and public service programs, along with broadcasting on social media platforms like YouTube and Instagram, helping TVRI Jambi sustain its public broadcaster role through digital engagement. However, limited resources for live broadcasts and a shortage of skilled personnel pose significant challenges to full implementation in the field.